Over a million students use our free study notes to help them with their homework
a^2 + b^2 = c^2c^2 = 8^2 + 6^2c^2 = 64 + 36c^2 = 100c=10
Since there is a common factor of 3 on the the left hand side of the equation, you can take that out as a factor:3(x^2 + 2x +1) = 0Then you you can divide both sides by 3:x^2 + 2x + 1 = ...
To answer this question it is best to remember SOH CAH TOA.SOH: sin(angle)=opposite (length of side opposite the angle)/hypotenuse (length).CAH: cos(angle)=adjacent (length of side next to the angle)/hypo...
The first think you can do is look to see if all of your terms can be divided by a common factor. In this case it is 3, leaving you with 3(x^2 - 3x - 10). This can be factorised further to produce somethi...
You should start off by separating the brackets as the squared only applies to one of them. We'll deal with that one first. Write the (2x + 3y)^2 as two separate brackets of (2x+3y). Then multiply the fir...
←
404
405
406
407
408
→
Internet Safety
Payment Security
Cyber
Essentials